Effect of soil management and biofertilizer application on cocoa's flower and fruit development. Issue 1 (October 2020) - Kaimuddin; Nasaruddin; Darwis, D
Abstract: A research aimed to determine the effectiveness of tillage and biofertilizer on the development of flowers and fruit on cocoa ( Theobroma cacao . L). This research was conducted in Barang Village, Liliriaja Subdistrict, Soppeng Regency. The research was carried out based on a 2-factor factorial design with randomized block design (RBD) as the basic design. The first factor was soil tillage which consisted of 4 levels namely; without tillage and without mulch; organic mulch without tillage; tillage without mulch, tillage and organic mulch. The second factor was biofertilizer application which consisted of 4 levels, namely: without biofertilizer, biofertilizer 1 cc.L −1, biofertilizer 1.5 cc.L −1, and biofertilizer 2 cc.L −1 . Therefore, there were 16 treatment combinations that were repeated 3 (three) times and each unit consisted of 4 plants making a total of 192 plants. The results indicated that the biofertilizer g3 (2 cc.L −1 ) and g2 (1.5 cc.L −1 ) provided the highest average of the formed fruit nipples (127), falling fruit nipples (50.00), survived fruit of 10-12 cm (77), harvested fruit (24.58), dry weight of 100 seeds (96.10) and pod index (22.80). The interaction was shown on the parameter of highest number of seeds with 2 cc L-1 of biofertilizer application (32.96).